Systemic Drivers of Corporate Tax Avoidance: A Narrative Review - Putri, Marissa Disthy; Florenstina (Indonesian Scientific Publication, 2025)
Corporate tax avoidance has emerged as a pressing global issue, driven by globalization, digitalization, and systemic vulnerabilities within national and international fiscal regimes. This study presents a narrative review aimed at synthesizing empirical and theoretical insights into the ethical, legal, policy, governance, and macroeconomic determinants of corporate tax avoidance. Literature was collected from Scopus, Web of Science, and Google Scholar, using targeted keywords and Boolean operators to capture a comprehensive range of peer-reviewed studies. Inclusion criteria emphasized empirical, conceptual, and policy-oriented works published between 2000 and 2025. The findings reveal that ethical commitments, particularly ESG integration and board diversity, reduce tax avoidance, while legal mechanisms such as IFRS adoption and whistleblower protections enhance transparency. Public policy reforms and environmental regulations shape corporate strategies but often have uneven impacts across jurisdictions. Governance structures show mixed effects, with independent boards constraining avoidance and state ownership often intensifying it. Macroeconomic pressures, including debt ratios and global crises, further condition corporate behavior. The discussion emphasizes systemic weaknesses such as corruption and policy instability as key enablers of avoidance, underscoring the need for stronger international coordination and methodological innovation in future research. The review concludes that achieving fiscal equity requires integrated strategies combining legal enforcement, policy harmonization, and ethical corporate governance.